Navigating the Digital Shift: Challenges and Solutions in Translator and Interpreter Training in Algeria - Rami Bououden; Saida Kohil (أنساق, 2025)
The Fourth Industrial Revolution has remarkably transformed the translation and interpreting education field. It has introduced newer and more advanced technologies that have affected translator and interpreter training strategies, bringing in more innovative technological tools, artificial intelligence, and digital learning platforms. This research paper investigates the integration of translation and interpreting technologies in academic training at the High Arab Institute of Translation in Algiers. It uses a mixed-methods approach, combining quantitative data from a questionnaire and qualitative information from verbal reports. The sample consisted of 24 students and alumni from the institute who completed the questionnaire, while the researchers collected verbal reports from other students and teachers as a complementary method. The results indicate that participants are aware of the benefits of technology in their field. However, insufficient practical training, flawed technological infrastructure, and insufficient exposure to advanced tools affected their experiences. As many expressed skepticism towards using Artificial Intelligence (AI) to generate translations, others voiced doubts concerning using technological aids in simultaneous interpreting. These findings underscore a need for curriculum enhancements to align Algerian training programs with industry standards and prepare students for a technology-driven job market. Finally, the study emphasizes the need to find solutions to prepare today’s translators and interpreters by equipping them with technological and digital skills, enabling them to manage the vast amount of data and succeed in the ever-evolving digital market.